2012
DOI: 10.1590/s1516-18462012005000013
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de falhas na triagem auditiva em escolares

Abstract: OBJETIVOS: determinar a ocorrência de falhas na triagem auditiva em escolares e comparar os resultados obtidos nas escolas da rede pública com os da particular. MÉTODO: participaram deste estudo de frequência, 90 escolares matriculados em uma escola da rede pública e outra da rede particular. Os alunos foram submetidos à meatoscopia e às emissões otoacusticas, verificando a influencia das variáveis sexo e rede de ensino aos resultados da triagem auditiva. RESULTADOS: foi constatado que 62,2% dos escolares pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
6
1
4
Order By: Relevance
“…Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…Among the tests used in different screening programs, the hearing assessment can be performed by using objective tests, such as the Otoacoustic Emissions (OAE) and the Tympanometry, which are both fast, non-invasive and reliable tests, thus representing an ideal test profile 10,11 . The OAE were first observed and described by Kemp 12 , who defined them as the release of sound energy originated in the cochlea, which propagates through the middle ear until it reaches the external auditory canal (EAC).…”
Section: This Study Was Approved By the Research Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, speech language therapy practice in schools held by Brazilian language speech therapists are based on some guidelines, such as screenings, counseling and referrals to restricted groups in the population considered at risk for diseases and disorders. Following this clinical tendency, several research studies still focus on students' disorder detection and discussion [4][5][6][7][8] , not on speech-language health promotion and literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant to this view grounded on clinical actions for the so-called school-related disorders, since the end of the last century, concerning health promotion and literacy, it can be pointed out another theoretical-methodological tendency which conceives the speech language pathologist as a mediator and co-author in the elaboration and development of language promotion-related actions in the educational context [3][4][5][6][7][8][9][10] . From this conception, speech language pathologists started to think about their work in school settings by means of actions which contemplate a partnership between them and the teachers, recognizing teachers' social role and knowledge, and including themselves in the political-pedagogic project of schools, enabling a deeper, jointed reflection on the involved educational aspects, specially the appropriation of oral and written language.…”
Section: Introductionmentioning
confidence: 99%